(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the problems of investigating typological and translatalogical aspects of the phraseological units verbalized by direct addresses in such non-related languages as Modern English and Uzbek, in which for the first time there have been revealed five main communicative-pragmatic types of the compared units and effective ways of translating them from one language into the other.